The reproducible radio outbursts of SS Cygni - Russell, T.; Miller-Jones, James; Sivakoff, G.; Altamirano, D.; O'Brien, T.; Page, K.; Templeton, M.; Körding, E.; Knigge, C.; Rupen, M.; Fender, R.; Heinz, S.; et al. (Oxford University Press, 2016)
We present the results of our intensive radio observing campaign of the dwarf nova SS Cyg during its 2010 April outburst. We argue that the observed radio emission was produced by synchrotron emission from a transient radio jet. Comparing the radio light curves from previous and subsequent outbursts of this system (including high-resolution observations from outbursts in 2011 and 2012) shows that the typical long and short outbursts of this system exhibit reproducible radio outbursts that do not vary significantly between outbursts, which is consistent with the similarity of the observed optical, ultraviolet and X-ray light curves. Contemporaneous optical and X-ray observations show that the radio emission appears to have been triggered at the same time as the initial X-ray flare, which occurs as disc material first reaches the boundary layer. This raises the possibility that the boundary region may be involved in jet production in accreting white dwarf systems. Our high spatial resolution monitoring shows that the compact jet remained active throughout the outburst with no radio quenching.